Analysis of health services cost at the dental clinic of the San Marcos University. - Madrid Chumacero, Marco Tulio (2006)
The objectives of this study were: To establish the unitary services cost in Dentistry, To describe simplest way to determine the costs structure approximated for each dental service offered at the clinic. They it was compared with the welfare rates at the dental clinic of the UNMSM, the results were the following ones: 1. Diagnosis: in the four cost activities is higher compared with the official rates, demonstrating "minimum utilities" that goes up from 0,21 to s. 15.96. 2. Radiology: in the cost eight activities is also higher compare with the official rates utilities goes up from S/.2.27 to s. 23.87. 3. Surgery: in fifteen activities it utilities goes up from S/. 141 to S/.43.64 4. Endodontia, of seven activities is appraised that official rates are below the costs and goes up from 9,7 to s.- 21.4 5. Periodontia: in eight activities the utilities oscillate from 6,13 to S/. 26.76, being observed loss in the following activities: Phase I, in Phase III. 6. Chrildren's dentistry: in four observed activities we have utilities that go up from S/.7.59 to S/.12.42 7. Prosthesis: In two activities utilities go from 1,08 to s. 63.77 8. Orthodontia, of 5 programmed activities all the tariffs are below the obtained costs (- S/.13.52 to - S/.43.52) 9. Occlusion the cost among three activities demonstrate utilities that goes from S/.14.36 to S/.31.39. 10. Cariology: in six activities the utilities oscillate between S/.2.10 and S/. 5.51